Women’s Access to Justice in Intimate Partner Violence in Bangladesh: A Legal Perspective - Nahar, Azizun (CenRaPS Journal of Social Sciences, 2024)
The number of intimate partner violence against women is increasing in Bangladesh. The remedy for intimate partner violence victims from social, legal, and psychological aspects requires proper research and practical action with remedy ensuring women's rights in modern times. The existing legal system of Bangladesh, in these respects, lacks adequate access to justice for women victims of intimate partner violence. So, their social, economic, psychological, and sexual issues are somehow ignored to be embodied in the relevant laws of the country for ensuring justice for the deprived group of people like women. In other words, their sufferings remain static, and they have no hope of a healthy, happy, and balanced life. More surprisingly, this victim group is neither aware of the problem involved with their life nor they are proactive in having an effective remedy thereon. Employing qualitative research methodology, the study aims to determine the effectiveness of existing legal remedies for the prevalent present social problem of intimate partner violence against women so that access to justice can be ensured.